THE PHENOMENON OF WIVES SUING FOR DIVORCE: A STUDY IN INDONESIA-MALAYSIA BORDER COMMUNITIES IN SAMBAS, WEST KALIMANTAN - Asman (Jurnal Syariah, 2024)
This study examines the legal claims made by wives to their husbands from the perspective of the Indonesia-Malaysia border community in Sambas, West Kalimantan. Maṣlaḥah al-ḍaruriyyah, maṣlaḥah tahsiniyyah, and maṣlaḥah hajiyyah served as the foundation for this investigation. This study examines the legal claims made by wives to their husbands from the perspective of the Indonesia-Malaysia border community in Sambas, West Kalimantan. Maṣlaḥah al-ḍaruriyyah, maṣlaḥah tahsiniyyah, and maṣlaḥah hajiyyah served as the foundation for this investigation. Qawl jadid claims that the Imam Shafi‘i talaq ba’in sughra school is also known as khulu‘, wherein a husband must obtain a new marriage contract in order to reunite with a woman who has become mentally ill due to ba’in sughra and is prohibited from making amends with her during the period of ‘iddah. The research topic, which asks: What is the benefit of the wife’s lawsuit to the husband from the standpoint of maṣlaḥah?, develops the subject matter in order to make this study focused and methodical. This kind of qualitative research uses an Islamic legal perspective while doing fieldwork. The Malay Sambas community, who commit divorce, is the study’s informant. According to the findings of the study, that (2) There is a shift in times or lifestyles where the values of marital justice are no longer applied in marriage such as ignoring religious rules, knowing the law but not obeying the law only as a formality so that it is easy to divorce, (3) the involvement of the Legal Aid Institute and the Legal Aid Post in the divorce process of married couples to be cheerful.